Developing a novel computationally designed impedimetric pregabalin biosensor - Gholivand, Mohammad Bagher (2014)
A computationally designed impedimetric pregabalin (PGB) biosensor based on immobilization of bovine serum albumin (BSA) onto graphene/glassy carbon electrode (BSA/Gr/GCE) has been developed using initial characterization by computational methods and complementing them by experimental observations. Computational results showed that the BSA hydrophobically binds to Gr which is energetically favorable and leads to the spontaneous formation of the stable nanobiocomposite (BSA/Gr), and also showed that the interaction of PGB with BSA is mainly driven by hydrogen bonding and hydrophobic interactions. The interactions of BSA with Gr and PGB with BSA were also monitored by fluorescence and UVvis spectroscopic techniques, and their results were consistent with the computational results. The electrochemical properties of the fabricated composite electrodes were examined by cyclic voltammetry (CV) scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS) techniques. Besides complementing the computational studies, experimental results showed that the addition of Gr to the surface of the electrode facilitated the electron transfer reactions, and also showed that the presence of BSA inhibits the interfacial electron transfer in some extent due to the non-conductive properties of BSA. The presence of the PGB may form an electroinactive complex with BSA which decelerates the interfacial electron transfer leading to obvious faradaic impedance changes. The faradaic impedance responses were linearly related to PGB concentration between 10.0 nM and 280.0 nM and the limit of detection (LOD) was calculated to be 3.0 nM (3Sb/b). Finally, the proposed biosensor was successfully applied to determination of PGB in human serum samples. The results were satisfactory and comparable to those obtained by applying the reference method based on high performance liquid chromatography (HPLC). The results confirmed that the proposed biosensor has good sensitivity, selectivity, stability, repeatability, reproducibility, and regeneration ability for PGB determination.